Impact of Typhoon on Coastal Upwelling Off The Eastern Hainan Island: A Case Study of Typhoon Rammasun (2014) - Hong, Bo; Huang, Xiongxing; Liu, Sumin; Xu, Hongzhou (Frontiers in Marine Science, 2022)
The coastal upwelling (HIU hereafter) off the eastern Hainan Island (EHI) is an important phenomenon in the northern South China Sea. Though this phenomenon has been extensively studied, the fast responses of its inner oceanic processes to typhoon passage remain unclear. Based on satellite data and a validated three-dimensional numerical model, the HIU responses to the passage of Typhoon Rammasun (2014) are explored in this study. Impacted by Rammasun, the climbing of deep water off the EHI was depressed and the bottom cold water moved seaward for at least 10 km. Though the HIU was weakened, a cooling event and Chl-a bloom in the HIU were formed after the passage of Rammasun. Diagnostic analyses reveal that both advection and diffusion terms put compatible contributions to controlling the local rate of temperate change during the typhoon passage. And the advection terms showed significant internal wave signals along the shelf break off southeastern Hainan Island. At the same time, strong near-inertial waves (NIWs) with 0.705 cpd were triggered in the HIU. The near-inertial waves (NIWs) lasted for about two weeks and caused strong vertical mixing in the HIU after Rammasun. Overall, typhoon wind and NIWs combined to dominate temperature variation in the HIU during the typhoon period.